2012
DOI: 10.1016/j.rmed.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Major respiratory adverse events after laparascopic gastric banding surgery for morbid obesity

Abstract: Although laparoscopic adjustable gastric banding surgery has few short-term risks and is highly effective at achieving weight reduction, we found an increased risk for major respiratory complications in the long-term period. The obesity epidemic and the increased use of surgical techniques to treat obesity will most likely lead to an increase in the incidence of long-term post-operative respiratory complications. This entity is probably under-reported and needs further research into how to reduce its incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
10
2
1
Order By: Relevance
“…Respiratory complications are one of the main concerns in obese perioperative patients, with major adverse respiratory events reported to occur in ∼2% of large overall bariatric cohorts. 32 In our cohort, the respiratory complication rate (12.5%) was still lower than the previously reported range of 14.4-28.2% in two smaller and older ICU studies. 12 33 Hellings and colleagues reported pulmonary co-morbidity was associated with increased risk of prolonged mechanical ventilation >24 h in 60 bariatric patients admitted to ICU.…”
Section: Discussioncontrasting
confidence: 69%
“…Respiratory complications are one of the main concerns in obese perioperative patients, with major adverse respiratory events reported to occur in ∼2% of large overall bariatric cohorts. 32 In our cohort, the respiratory complication rate (12.5%) was still lower than the previously reported range of 14.4-28.2% in two smaller and older ICU studies. 12 33 Hellings and colleagues reported pulmonary co-morbidity was associated with increased risk of prolonged mechanical ventilation >24 h in 60 bariatric patients admitted to ICU.…”
Section: Discussioncontrasting
confidence: 69%
“…The analysis of mortality of 13,871 patients in Italy after bariatric surgery showed 11.8% were due to respiratory failure including pulmonary embolism [66], (L2+). Not only LRYGB, but also LAGB was associated with major respiratory complications of aspiration pneumonia, atelectasis, exacerbation of asthma and empyema and lung abscess [67], (L2+). Prediction of patients who are likely to develop respiratory complication and prevention was the corner stone in reducing this kind of complications.…”
Section: Resultsmentioning
confidence: 99%
“…Avriel et al [11], found life-threatening, post-LAGB pulmonary complications in 30 subjects (1.4%). The proportion of subjects in that study with serious post-operative pulmonary complications is close to the proportion of subjects hospitalized due to a respiratory condition following surgery in the current study (1.1%).…”
Section: Discussionmentioning
confidence: 97%